Relationship between the Profile of Agricultural Students and their Career Aspiration about Prospects of Agripreneurship - Jayasudha J; R. M. Naik; Kalpesh L. Chaudhary (Archives of Current Research International, 2024)
Career aspiration refers to a long-term professional aim or goal that a person sets for themselves in their chosen career or profession. Aims: To ascertain the relationship between the profile of students and their career aspiration about prospects of agripreneurship. Study Design: Expost facto research design. Place and Duration of Study: The study was taken at four State Agricultural Universities of Gujarat. August 2023 – March 2024. Methodology: The study was conducted among the students from the agriculture faculty in four State Agricultural Universities of Gujarat which are Navsari Agricultural University, Junagadh Agricultural University, Anand Agricultural University and Sardarkrushinagar Dantiwada Agricultural University. The respondents were M.Sc. (Agri.), Ph.D. (Agri.) and final year B.Sc. (Agri.) students from the main campus of each university. Expost facto research design was used. By simple random sampling technique, 25 students from each degree from four universities were selected. Thus, the total sample is 300. By interview method, responses were collected using an interview schedule. The relationship between the independent and dependent variable were analysed using statistical tools such as correlation and stepwise regression. Results: The variables such as age, source of information, risk taking ability, achievement orientation, leadership ability, critical thinking, self-confidence and innovativeness were significantly correlated with the level of career aspiration about prospects of agripreneurship at 1 per cent level of significance. The variables such as the source of information, achievement orientation, critical thinking, innovativeness and age were accounting influences and 41.00 per cent variation in career aspiration of the students. Conclusion: Hence, these variables should be taken care and need to improve for the change in career aspiration.